Interpol's forensic science review - Daeid, Niamh Nic , 1967-; Houck, Max M. (CRC Pres, 2010)
Every three years, worldwide forensics experts gather at the Interpol Forensic Science Symposium to exchange ideas and discuss scientific advances in the field of forensic science and criminal justice. This book provides a comprehensive literature review of each of the subject areas